FEARS AND ASSUMPTIONS IN THE PANDEMIC CRISIS IN HUNGARY: Received: 13th October 2022 Revised; 29th October 2022; 1st November 2022; 2nd November 2022 Accepted: 11th November 2022 - Varga, Janos; Csiszárik-Kocsir, Agnes (PEOPLE: International Journal of Social Sciences, 2022)
The pandemic that erupted and escalated in 2020 has brought unprecedented changes to our daily lives. The new situation has challenged everyone. We have had to face unprecedented constraints, change the way we used to work, and experience a new level of uncertainty. Not only households but also businesses and entrepreneurs faced serious problems. Businesses were faced with a huge challenge in terms of disrupted supply chains and the loss of labor. Jobs were lost and jobs became precarious as a result of the pandemic. All these challenges proved to be not only livelihood but also psychologically stressful for the average person. Many feared for their economic livelihoods and even worried about their health. In this study we want to show what were the fears and worries people had about the overnight austerity measures in 2020 and the unprecedented pandemic emergency, according to the results of a primary survey conducted in Hungary.